2019
DOI: 10.1016/j.physletb.2019.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Fractional-order phase transition of charged AdS black holes

Abstract: Employing the fractional derivatives, we construct a more elaborate classification of phase transitions compared to the original Ehrenfest classification. In this way, a thermodynamic system can even undergo a fractional-order phase transition. We use this method to restudy the charged AdS black hole and Van der Waals fluids and find that at the critical point they both have a 4/3-order phase transition, but not the previously recognized second-order one.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…When β > 4/3, the ß-order fractional derivatives of the Gibbs free energy diverge. Hence, as for 4D RN-AdS black holes [1], the FPT order of the RN-AdS black hole surrounded by quintessence is β 4/3. This is clearly illustrated by the left panel of Figure 1 where the fractional derivative D β t g is plotted as a function of the reduced temperature t for several values of β: β 9/6, 9/8, and 4/3 near the critical point.…”
Section: Charged Ads Black Hole Surrounded By Quintessencementioning
confidence: 89%
See 1 more Smart Citation
“…When β > 4/3, the ß-order fractional derivatives of the Gibbs free energy diverge. Hence, as for 4D RN-AdS black holes [1], the FPT order of the RN-AdS black hole surrounded by quintessence is β 4/3. This is clearly illustrated by the left panel of Figure 1 where the fractional derivative D β t g is plotted as a function of the reduced temperature t for several values of β: β 9/6, 9/8, and 4/3 near the critical point.…”
Section: Charged Ads Black Hole Surrounded By Quintessencementioning
confidence: 89%
“…The generalized Ehrenfest classification holds for all thermodynamic systems having phase structures, including AdS black holes with analogous behavior to Van der Waals gases. Indeed, a first study recently performed by Ma [1] showed that RN-AdS black holes can undergo 4/3 order FPT. In this paper, we aim to explore further this issue and see whether this fractional order holds for any AdS black hole solution, as in VdW systems.…”
Section: Introductionmentioning
confidence: 99%
“…One naturally wonders how this fluctuation of y max compares with the mean of the separation between the scaled positions of the rightmost and the second rightmost particles denoted as ∆ edge . The N dependence of this average separation at the edge § Alternatively, the Ehrenfest classification [62][63][64] can be generalised by extending the notion of normal derivatives to fractional derivatives [65][66][67] can be obtained using the "Lifshitz argument", which is frequently used in extreme value statistics [14,17]. According to this argument…”
Section: Distribution In the Typical Regionmentioning
confidence: 99%
“…
In this paper, we have extended and deepened the study on fractional order phase transition (FPT) of a charged AdS black hole performed in [1]. We have carried out a detailed analysis of FPT for three AdS black hole prototypes: black hole surrounded by quintessence background, 5D Gauss-Bonnet, and lastly Kerr black holes.
…”
mentioning
confidence: 99%
“…The generalized Ehrenfest classification holds for all thermodynamic systems having phase structures, including AdS black holes with analogous behaviour to Van der Waals gases. Indeed, a first study recently performed by Ma [1] showed that RN-AdS black holes can undergo 4/3 order FPT. In this paper, we aim to explore further this issue and see whether this fractionnal order holds for any AdS black hole solution, as in VdW systems.…”
mentioning
confidence: 99%